Analysis of an MMAP/PH1, PH2/N/[ the sign of infinity] queueing system operating in a random environment - Kim, Chesoong; Dudin, Alexander; Dudin, Sergey; Dudina, Olga (Zielona Góra: Uniwersytet Zielonogórski)
A multi-server queueing system with two types of customers and an infinite buffer operating in a random environment as a model of a contact center is investigated. The arrival flow of customers is described by a marked Markovian arrival process. Type 1 customers have a non-preemptive priority over type 2 customers and can leave the buffer due to a lack of service. The service times of different type customers have a phase-type distribution with different parameters.
Keywords: random environment; marked Markovian arrival process; phase-type distribution; Laplace-Stieltjes transform